2012
DOI: 10.12820/rbafs.v.16n1p5-10
|View full text |Cite
|
Sign up to set email alerts
|

Intervenção Do Profissional De Educação Física Nos Núcleos De Apoio À Saúde Da Família Em Municípios Do Norte Do Paraná

Abstract: O objetivo deste estudo foi verificar as características de intervenção dos profissionais de Educação Física inseridos no Núcleo de Apoio à Saúde da Família (NASF). A amostra foi composta por sete profissionais que atuavam em municípios da região norte do estado do Paraná. Foi realizada uma entrevista semi-estruturada que foi gravada e transcrita posteriormente. Para analise das entrevistas foi utilizado elementos da analise de conteúdo através do sistema de categorias. Todos os profissionais formaram-se em Ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
64

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 9 publications
2
9
0
64
Order By: Relevance
“…The main three were: 1) more options of physical spaces for the development of physical activity practices; 2) supporting fewer family health teams; 3) increasing and improvement of materials for the development of physical activity practices. In agreement with these findings, Physical Education professionals working in NASF of the northern region of Parana reported the main difficulty to develop physical activity practice is lack of physical space 6 . Related to the problem of material resources, professionals in Parana reported using alternative materials for being low cost options (for example, weights made of plastic bottles filled with sand or rocks and brooms as sticks.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The main three were: 1) more options of physical spaces for the development of physical activity practices; 2) supporting fewer family health teams; 3) increasing and improvement of materials for the development of physical activity practices. In agreement with these findings, Physical Education professionals working in NASF of the northern region of Parana reported the main difficulty to develop physical activity practice is lack of physical space 6 . Related to the problem of material resources, professionals in Parana reported using alternative materials for being low cost options (for example, weights made of plastic bottles filled with sand or rocks and brooms as sticks.…”
Section: Discussionsupporting
confidence: 75%
“…The development of the questionnaire followed three steps: 1) group discussion on which questions would have theoretical base according to other studies in intervention by Physical Education professionals within SUS, National Policy in Health Promotion and NASF guidelines 2,5,6,7,8 . The discussions were led by researchers of the Physical Activity Epidemiology Group -University of São Paulo (GEPAF-USP) and the Research Group in Lifestyles and Health of the University of Pernambuco (GPES-UPE); 2) consolidation of the questions as a products of the previous reunions within the groups; 3) pre-test with Physical Education professionals working in the NASF.…”
Section: Instruments Used In the Researchmentioning
confidence: 99%
“…A falta de estrutura física também já foi associada a dificuldades para a realização das atividades na Atenção Básica (FORMIGA; RIBEIRO, 2012). Uma das dificuldades citadas pelos profissionais de Educação Física no NASF para a realização das atividades consistiu justamente na ausência de espaços adequados (SOUZA;LOCH, 2011).…”
Section: Discussionunclassified
“…The NASF guidelines stress that physical education professionals should develop activities addressing the various elements of the body movement culture, encouraging the treatment of chronic diseases and increasing the level of physical activity 10 . The Health in the Square Project developed in 55 sites in the city of Araraquara / SP showed that there is good acceptance by adults and older adults to Lian-Gong and Tai Chi Chuan activities 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies with NASF teams in southern Brazil indicate that the educational practices developed by Physical Education professionals are mostly limited to intervention in groups, prescriptive in nature and focused on the disease 9,10 . The information in this study reflects the implementation of NASF in the country and the challenging role implicit in this proposal for Physical Education, since there is lack of knowledge of the profession about the dynamics of working in a matrix team of APS.…”
Section: Introductionmentioning
confidence: 99%